CLAPO syndrome. Case report and literature review. - Mazzotta, F. (European Journal of Pediatric Dermatology, 2023)
CLAPO is a recently reported syndrome characterized by capillary malformation of the lower lip, lymphatic vessel defects of the face and neck, asymmetry of the face and of the limbs and partial or generalized overgrowth. In the actual report a new case of CLAPO syndrome was described and a review of the 28 cases present in the literature was performed.